PERANAN PENYULUH DAN STRATEGI PENINGKATAN PERANAN PENYULUH PERKEBUNAN DALAM PENGEMBANGAN KELOMPOK TANI PEMASARAN KARET DI KABUPATEN KUANTAN SINGINGI - Syafriwan Syafriwan; Syaiful Hadi; Rosnita Rosnita (DINAMIKA PERTANIAN, 2013)
The aim of this research was to analyze the role of plantation extension in develeopment of rubber marketing group and formulate strategy to increase extension role for developing rubber marketing group in Kuantan Singingi Regency. The amount of 5% of sample for each marketing group management and marketing group member was selected by purposive and random methods, respectively. The result showed that extension personnel in Kuantan Singing had role in organizing dan dinamizing farmer group, besides being as technical and consultant in directing farmer group for marketing rubber. In rubber marketing, extension personnel teached the marketing and farming techniques throught trainning according to competency and skill owned. Extension plantation personnel had a role in developing rubber marketing group which was proved by the organzed farmer group and improved farmer income. Farmers which joined in farmer group had more enthusiasm in increasing performance on their farmer group. The strategy which could applied extension personal in developing rubber marketing group consisted of three main priorities, i.e, 1) to make group cooperation for marketing rubber to available market, 2) to increase rubber quaity for maitin selling price, and 3) to cut coopeation relationship to “toke” with empowering capital of the farmer groups.